Competence, performance and trainability of older workers of higher educational institutions in Malaysia - Wok, Saodah; Hashim, Junaidah (Emerald Publishing, 2014)
Purpose – The purpose of this paper is to investigate the competence, performance, and trainability of older workers of higher educational institutions in Malaysia. Design/methodology/approach – Survey methods were used in this study. The survey measures were adopted from Rothwell (2002) and Sarmiento et al. (2007) for performance and competence, respectively, while trainability measurements were adopted from Maurer et al. (2008). The sample of 325 respondents consisted older workers in the higher education sector aged between 55 and 60 years old. Findings – Based on the assessments made by the older workers themselves and their superiors, it is found that the older workers are competent, performing well, and are trainable. The administrative older staff, however, were rated lower by the superior as compared to the academic older staff. This may be due to the fact that most of the assessors are academicians. Regardless of the category of the staff, performance of older workers is positively related to their competence and trainability. Research limitations/implications – Competence and trainability are important factors as they are found related to performance. This study focuses on education sector. It would be interesting to include older workers from other sectors because the education sector is perceived to be less physically demanding. Practical implications – This study provides valuable insights into considering of revising the retirement age of academician in higher education sector even higher. Age seems to be an advantage to this group of employees. Originality/value – This study is unique and significant because it focuses on important sector, i.e. higher education. It would reduce the knowledge gap in performance management of older workers especially in higher education sector.